(untitled) (Perner’s Contacts, 2016)
The paper is focused on hazardous materials transportation by road and investigates risk factors influencing risk associated with such transportation. Statistical data on this special type of transportation are used in order to detect most important factors, increasing accident probability. Paramount attention is devoted to the drivers and factors causing the accidents. Measures reducing risk of hazardous material transportation are proposed in this paper.